Application of Boiling Water from Salam Leaves (Synzigium Polyanthum) And Cinnamon (Cinnamomun Burmanii) on Hypertension Patients - Muda, Iskandar; Susanti, Annisa Aprillia; Sukmana, Mayusef; Khumaidi, Khumaidi (Jurnal Kesehatan Pasak Bumi Kalimantan, 2024)
Background: Hypertension is having a condition where high blood pressure is ≥140/90 mmHg. Hypertension has treatment in the form of herbal therapy. Herbal therapy that can be applied is by consuming water boiled with bay leaves (S. polyanthum) and water boiled with cinnamon (C. burmannii). The ingredients contained in bay leaves (S. polyanthum) and cinnamon (C. burmannii) have benefits for hypertension sufferers, namely, they can help reduce high blood pressure. Objective: The research aims to know the description before and after the application of bay leaf (S. polyanthum) and cinnamon (C. burmanii) boiled water. Method: This research used a descriptive method with a case study approach which was carried out in July 2023 with two respondents with grade 2 hypertension in the Baqa health center area using the SOP for boiled water from bay leaves (S. polyanthum) and cinnamon (C. burmanii). Result: Blood pressure R1 = 173/102 mmHg before being given bay leaf boiled water therapy (S. polyanthum) and blood pressure R2 = 178/107 mmHg before being given cinnamon boiled water (C. burmanii). Blood pressure R1=153/109 mmHg after being given bay leaf boiled water therapy (S. polyanthum) and blood pressure R2=168/118 mmHg after being given cinnamon boiled water (C. burmanii) each once a day for five days. Conclusion: There is a decrease in blood pressure in hypertension sufferers after being given a concoction of boiled water from bay leaves (S. polyanthum) and cinnamon (C. burmanii).Keywords:  Bay Leaf (S. polyanthum) and Cinnamon (C. burmanii) Boiled Water, Blood Pres-sure, Grade 2 Hypertension.